Commodity Forward and Futures Contract: An Innovation in Islamic Derivatives - Nadhirah, Nordin; Rahimah, Embong; Normadiah, Daud (2014)
This paper attempts to analyze the innovation in Islamic forward and futures contracts of crude palm oil in Malaysia. Commodity forward and futures contracts are the most common types of derivative instruments, whose value depends on the value of the underlying assets, namely commodities. The emergence of forward and futures contracts resulted from the advancement of financial engineering that is based on conventional finance. Therefore, this study is significant in order to identify the extent to which conventional commodity forward and futures contracts meet the principles outlined by the shari’ah in the discipline of Islamic finance. Initially, this study analyzes the shari’ah issues in commodity forward and futures crude palm oil and subsequently, it proposes a set of potential shari’ah principles in the contracts. This study uses a thematic analysis approach in analyzing the data obtained from secondary sources and interviews with several selected respondents who are involved in this industry. The result has shown that the contract raised several shari’ah issues such as gharar, speculation and gambling. Finally, this study recommends the application of the principle of wa'd and bay almurabahah/musawamah as an innovation in shari’ah compliant commodity forward and futures contracts.